2023
DOI: 10.2147/idr.s410593
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Diagnosis Value of Nanopore Sequencing in Severe Hospital-Acquired Pneumonia Patients

Abstract: Background Next-generation sequencing of the metagenome (mNGS) is increasingly used in pathogen diagnosis for infectious diseases due to its short detection time. The time for Oxford Nanopore Technologies (ONT) sequencing-based etiology detection is further shortened compared with that of mNGS, but only a few studies have verified the time advantage and accuracy of ONT sequencing for etiology diagnosis. In 2022, a study confirmed that there was no significant difference in sensitivity and specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Detection of viruses also has implications for antimicrobial stewardship and with increasing antiviral agents available, the appropriate stratification of patient management. Several studies have previously compared Illumina and ONTbased metagenomics of bacterial and fungal mock communities (29,30,32), simulated bacterial datasets (32,33,38) and clinical samples (18,28,71,72). Some work on viral detection from clinical samples (27,(73)(74)(75)(76)(77) or mock communities resembling environmental samples (34) has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of viruses also has implications for antimicrobial stewardship and with increasing antiviral agents available, the appropriate stratification of patient management. Several studies have previously compared Illumina and ONTbased metagenomics of bacterial and fungal mock communities (29,30,32), simulated bacterial datasets (32,33,38) and clinical samples (18,28,71,72). Some work on viral detection from clinical samples (27,(73)(74)(75)(76)(77) or mock communities resembling environmental samples (34) has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Charalampous et al [38] optimized the pilot test, achieving 96.6% sensitivity and 41.7% specificity for pathogen detections, which were then confirmed by quantitative PCR and pathobiont-specific gene analysis, increasing to 100% specificity and sensitivity. Another comparative analysis revealed a rapid pathogenic identification of the nanopore sequencing method, of which the detection time was 2.4 fold and 13 fold lower than those of the MGISEQ-2000 platform (BGI-Tianjin, Tianjin, China) and traditional culture method, respectively [31]. These studies revealed the advantages of the nanopore sequencing method as a rapid and accurate tool for pathogenic detection.…”
Section: Nanopore Sequencing Technology In Pathogenic Diagnosticsmentioning
confidence: 91%
“…The nanopore sequencing method can be applied to different types of sequencing, such as metagenomic sequencing, whole-genome sequencing, and targeted sequencing, because of the diversity of kits for library preparation (Figure 3) [28]. These three sequencing types are effective in the detection of different pathogens, including bacteria, fungi, viruses, and parasites [29][30][31][32][33][34]. For example, a nanopore-sequencingbased workflow was developed to identify fungal communities in clinical samples of pneumonia patients (Figure 4) [29,34].…”
Section: Nanopore Sequencing Technology In Pathogenic Diagnosticsmentioning
confidence: 99%
“…Nanopore sequencing is a highly effective molecular diagnostic test that has gained significant popularity in various fields, including infectious diseases. 35 It has emerged as a valuable tool for the rapid diagnosis of TB and drug susceptibility testing, particularly for drug-resistant TB. 36 Although nanopore sequencing plays a crucial role in the rapid diagnosis of PTB, there is limited research focusing on its application in smear-negative PTB, particularly with large sample sizes.…”
mentioning
confidence: 99%